Anolis lizards as biocontrol agents in mainland and island agroecosystems. Issue 7 (2nd March 2017) - Monagan, Ivan V.; Morris, Jonathan R.; Davis Rabosky, Alison R.; Perfecto, Ivette; Vandermeer, John
Abstract: Our knowledge of ecological interactions that bolster ecosystem function and productivity has broad applications to the management of agricultural systems. Studies suggest that the presence of generalist predators in agricultural landscapes leads to a decrease in the abundance of herbivorous pests, but our understanding of how these interactions vary across taxa and along gradients of management intensity and eco‐geographic space remains incomplete. In this study, we assessed the functional response and biocontrol potential of a highly ubiquitous insectivore (lizards in the genus Anolis ) on the world's most important coffee pest, the coffee berry borer ( Hypothalemus hampei ). We conducted field surveys and laboratory experiments to examine the impact of land‐use intensification on species richness and abundance of anoles and the capacity of anoles to reduce berry borer infestations in mainland and island coffee systems. Our results show that anoles significantly reduce coffee infestation rates in laboratory settings (Mexico, p = .03, F = 5.13 df = 1, 35; Puerto Rico, p = .014, F = 8.82, df = 1, 10) and are capable of consuming coffee berry borers in high abundance. Additionally, diversified agroecosystems bolster anole abundance, while high‐intensity practices, including the reduction of vegetation complexity and the application of agrochemicals were associated with reduced anole abundance. The results of this study provide supporting evidence of the positive impact of generalist predators on the control of crop pests in agricultural landscapes, and the role of diversified agroecosystems in sustaining both functionally diverse communities and crop production in tropical agroecosystems. Abstract : The focus of this project was to assess the predatory function of wildlife in tropical coffee agroecosystems (i.e. pest reduction by a generalist insectivore), and the relative impacts of land‐use intensification on species abundance in mainland and island settings. The results of this study are the first to provide evidence that lizards in the genus Anolis are capable of both consuming the coffee berry borer in high numbers and significantly reducing infestations in laboratory settings. Our results show that anole presence is bolstered by vegetative complexity, and significantly reduced by high intensity practices including the application of agrochemicals.